THE ROLE AND PRACTICALITY OF FOLK AND ARTISTIC DECORATION IN THE DEVELOPMENT OF AESTHETIC CULTURE FOR STUDENTS (Academicia Globe: Inderscience Research, 2023)
The role and practical significance of folk art in the development of aesthetic culture, the specific functions of developing and developing aesthetic discipline in detail .